NURSING CONSULTATION TO DIABETES PATIENT IN A MILITARY HOSPITAL: A PRACTICE IN FRONT OF A PARADIGM CHANGING (Fiep Bulletin - online, 2013)
This is a integrative literature search, which were analyzed 12 articles concerning the consultation of Nursing to diabetic and the model of health existing in the country. Data were collected via the Internet, worked on databases of periodicals CAPES, LILACS and MEDLINE, using the descriptors Nursing, Diabetes, Consultation of Nursing and SUS. The objective was to make a reference survey to find out how the nurses are performing the practice of consultation with the nursing diabetic (based on Flexnerian paradigm or the paradigm of social production of health?) And use the result in the deployment of this practice in a military hospital. After reading the articles and analysis, it was found that the practice of consultation of nursing developed to people with diabetes is targeted to follow the paradigm of social production of health, education based on the individual and his family, in order to reduce complications associated with such chronic-degenerative disease.
Keywords: paradigm; nursing consultation; diabetes